PELATIHAN PEMBUATAN GAME EDUKATIF MENGGUNAKAN KAHOOT DAN WORDWALL - Khatrin Juliani Taku Neno; Aranci Amheka (Pengabdian Masyarakat Ilmu Pendidikan, 2023)
Rapid technological developments eventually also spread to the world of education and become an integral part of today's digital era. The use of integrated technology in learning media brings many benefits in the teaching and learning process. Educational games are one of the media that can be an alternative in improving the quality of learning. Popular and free platforms that can be used to create educational games are kahoot and wordwall.